Venture capital a wartość przedsiębiorstwa - Radawiecka, Ewa (Venture Capital vs. the Value of a Company, 2008)
A lot of companies declare that their superior goal in running a business is to maximise the value of a company that is visible for their owners as well as to use the methods of management that are mainly focused on the increase in the market value growth. The focus on the aforementioned methods of management may particularly refer to enterprises financed by institutional investors such as eg. venture capital funds. Venture capital is a short and long-term investment capital which is characterised by a large scale of hazard and future top ranking profits. That capital is an alternative for foreign sources of financing the assets.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 128-135